The entrenchment of Islamic cultures as the everyday conduct at the communal level - Wan Mohd Ghazali, Wan Norshira (2018)
This paper examines the entrenchment of Islamic cultures in the Malaysian society. Using constructivist grounded theory, in-depth face-to-face and focus group interviews data with 33 respondents from three different groups – government officers, media practitioners, and the general public – were analysed with the assistance of NVivo software. The study contends that the state is involved directly in the composition of cultures through its power structure. As Islam is not the only practising religion; a question to be explored is ‘what interpretation do people give to the construction and practices of Islam’? Most research deals with the broader role of Islam in Malaysian politics that the cultural implications and experiences of the religion in the society has not been specifically or substantively addressed and led to the peripheral notion of Islam. Therefore, this paper focuses on the cultural implications and experiences of Islam with the aim to extend the current research treatment of Malaysia’s Islamisation project. The results reveal that, when religious consciousness has increased, the Islamisation projects are no longer a mere political rivalry and state’s manipulation of power but more towards fulfilling the community’s need for stronger Islam. The paper will explore Islamic cultures as communally ‘everyday conducts’. The paper fits the cultural theme.